Brucella spp. Omp25 Promotes Proteasome-Mediated cGAS Degradation to Attenuate IFN-β Production - Li, Ruizhen; Liu, Wenli; Yin, Xiangrui; Zheng, Fangfang; Wang, Zhenyu; Wu, Xingchen; Zhang, Xiaohua; Du, Qian; Huang, Yong; Tong, Dewen (Frontiers in Microbiology, 2021)
Type I interferons (IFN-I), a kind of cytokine widely expressed in various tissues, plays important roles in anti-infection immunity. Yet, it is not defined whether Brucella spp. can interfere with type I interferon production induced by other pathogens. In this study, we investigated the regulatory roles of Brucella major outer membrane protein Omp25 in the induction of type I interferon, and found that Omp25 inhibited IFN-β induction and downstream IFN-stimulated genes (ISGs) expression induced by various DNA viruses or interferon-stimulatory DNA (ISD) in human, murine, porcine, bovine, and ovine monocyte/macrophages or peripheral blood mononuclear cells. Brucella Omp25 suppressed the phosphorylation of stimulator of interferon genes (STING) and interferon regulatory factor 3 (IRF3) and nuclear translocation of phosphorylated-IRF3 in pseudorabies virus (PRV)- or herpes simplex virus (HSV-1)-infected murine, human or porcine macrophages. Furthermore, we found that Brucella Omp25 promoted cyclic GMP-AMP synthase (cGAS) degradation via proteasome-dependent pathway, which resulted in a decreased cGAMP production and downstream signaling activation upon DNA viruses infection or ISD stimulation. Mapping the predominant function domain of Omp25 showed that the amino acids 161 to 184 of Omp25 were required for Omp25-induced cGAS degradation, among which five amino acid residues (R176, Y179, R180, Y181 and Y184) were required for the inhibitory effect of Omp25 on IFN-β induction. Taken together, our results demonstrated that Brucella Omp25 inhibits other pathogens-induced IFN-β expression via facilitating the proteasome-dependent degradation of cGAS in various mammalian monocyte/macrophages.